Etiology and Survival of Aplastic Anemia: A Study Based on Clinical Investigation - Jain, Dharmendra (J Clin Lab Anal, 2012)
BACKGROUND: Management of aplastic anemia is etiology driven, whether constitutional or acquired. Age, gender, and severity of disease also play crucial role in the survival of aplastic anemia. Since, inadequate data are available from India, the present study was conducted with the aim to evaluate the etiology and survival of aplastic anemia. METHODS: Three hundred patients were enrolled between May 2007 and April 2010. Severity analysis and chromosomal breakage study was performed and patients were followed up to calculate the survival rate. RESULTS: Only 9.4% of the cases demonstrated the evidence of constitutional disease. Patients with acquired disease showed a significantly higher odd ratio for hepatitis. Overall survival was found to be independent of the gender and inherited etiology. Phenotype resembling to constitutional disease was present in only 22.22% (6/27) of patients. Similar ratio of the constitutional and acquired disease in both the age groups was observed. CONCLUSION: Irrespective of the age and phenotype, chromosomal breakage study should be mandatory for all patients with aplastic anemia. Hepatitis as a preceding event may be associated with the cause of aplastic anemia. Young age and less severe disease were strongly associated with better survival. Lack of tertiary care facility in the country, time lag between diagnosis and treatment, and unaffordability to abide the treatment cost could be the major contributory factors for poorer survival.